AMTP: a multipath multimedia streaming protocol for mobile ad hoc networks - Rojviboonchai, K.; Yang, Fan; Zhang, Q.; Aida, H.; Zhu, W. (Institute of Electrical and Electronics Engineers, Inc., 2005)
Multipath streaming is a promising technique for multimedia transport over mobile ad hoc networks. In this paper, we propose AMTP, an ad hoc multipath streaming protocol for multimedia delivery. Coupled with a QoS multipath routing protocol, AMTP can accurately differentiate packet losses due to different network conditions, which is useful for real time multimedia streaming applications to perform correct error control and resource allocation. It also selects multiple maximally disjointed paths with best QoS to maximize aggregate end-to-end throughput. In case of path broken, AMTP can seamlessly switch to a proper path and therefore maintain high streaming quality. Simulation results demonstrate the effectiveness of the proposed AMTP.